ChemInform Abstract: Catalytic Asymmetric Torgov Cyclization: A Concise Total Synthesis of (+)‐Estrone. Issue 6 (February 2015) - Prevost, Sebastien; Dupre, Nathalie; Leutzsch, Markus; Wang, Qinggang; Wakchaure, Vijay; List, Benjamin
Abstract The highly Broensted acidic catalyst BIAC is used in the title reaction to produce various steroid derivatives and analogous ring systems under slightly modified conditions.